Engineered CRISPR/Cas13d Sensing hTERT Selectively Inhibits the Progression of Bladder Cancer In Vitro - Zhuang, Chengle; Zhuang, Changshui; Zhou, Qun; Huang, Xueting; Gui, Yaoting; Lai, Yongqing; Yang, Shangqi (Frontiers in Molecular Biosciences, 2021)
Aptazyme and CRISPR/Cas gene editing system were widely used for regulating gene expression in various diseases, including cancer. This work aimed to reconstruct CRISPR/Cas13d tool for sensing hTERT exclusively based on the new device OFF-switch hTERT aptazyme that was inserted into the 3’ UTR of the Cas13d. In bladder cancer cells, hTERT ligand bound to aptamer in OFF-switch hTERT aptazyme to inhibit the degradation of Cas13d. Results showed that engineered CRISPR/Cas13d sensing hTERT suppressed cell proliferation, migration, invasion and induced cell apoptosis in bladder cancer 5637 and T24 cells without affecting normal HFF cells. In short, we constructed engineered CRISPR/Cas13d sensing hTERT selectively inhibited the progression of bladder cancer cells significantly. It may serve as a promising specifically effective therapy for bladder cancer cells.